2015
DOI: 10.1002/adhm.201500224
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere‐Incorporated Hybrid Thermogel for Neuronal Differentiation of Tonsil Derived Mesenchymal Stem Cells

Abstract: Neuronal differentiation of tonsil-derived mesenchymal stem cells (TMSCs) is investigated in a 3D hybrid system. The hybrid system is prepared by increasing the temperature of poly(ethylene glycol)-poly(l-alanine) aqueous solution to 37 °C through the heat-induced sol-to-gel transition, in which TMSCs and growth factor releasing microspheres are suspended. The in situ formed gel exhibits a modulus of 800 Pa at 37 °C, similar to that of brain tissue, and it is robust enough to hold the microspheres and cells du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 68 publications
0
41
0
Order By: Relevance
“…In addition to their mesodermal differentiation potential (bone, cartilage, and fat), it was verified that TMSCs have the capacity to differentiate into endodermal lineage, expressing markers of parathyroid cells . Subsequently, other studies also identified differentiation capacities of TMSCs into various cell types, including myocytes , insulin‐releasing cells , neuron‐like or glial cells , tenocytes , and hepatocytes (Fig. ).…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to their mesodermal differentiation potential (bone, cartilage, and fat), it was verified that TMSCs have the capacity to differentiate into endodermal lineage, expressing markers of parathyroid cells . Subsequently, other studies also identified differentiation capacities of TMSCs into various cell types, including myocytes , insulin‐releasing cells , neuron‐like or glial cells , tenocytes , and hepatocytes (Fig. ).…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 82%
“…Similar to BM‐MSCs, TMSCs have a potential to differentiate into either neuron‐like or glial cells . In a 3D hybrid thermogel that fabricates growth factor‐releasing microspheres, TMSCs expressed phenotypes similar to immature neurons, exhibiting multipolar elongation with weak expression of neuronal markers such as neuronal growth factor, nuclear receptor‐related protein, and neuron‐specific enolase .…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%
“…Polymeric micro-and nanoparticles gained a lot of research interest over last decades as carriers for the controlled delivery of therapeutic peptides, vaccines, antibiotics [1][2][3], and for the purpose of cellular differentiation [4]. Several nanomaterials are already approved for medical applications, e.g., liposomes DoxilTM and polymeric micelles NanoxelTM for cancer treatment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The amino acids along the gelatin chain present numerous functional amino and hydroxyl groups as targets for surface modification or crosslinking reactions [26]. Glutaraldehyde [4,[27][28][29][30][31][32][33][34], genipin [35], and a water-soluble carbodiimide [36] are the widely used crosslinking agents for gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric MSs derived from synthetic sources are widely used in clinical applications because of their safety and biocompatibility . In recent times, MSs are used not only for drug delivery applications but also for the purpose of cellular differentiation . MSs coated with antibodies and peptides have been widely explored in the diagnosis of diseases as well …”
Section: Introductionmentioning
confidence: 99%